Answer:
b = -6
Explanation:
Given:
y=6x+b ----- (eq 1)
and
-3x+1/2y=-3 (Rearrange this equation to look likes eq (1) , add -3x to both sides)
(1/2) y = 3x - 3 (multiply both sides by 2)
y = 2(3x -3) (distribute the 2 into parentheses)
y = 6x - 6 -----(eq 2)
Recall that a system of equations will have an infinite number of solutions if both equations are the same line. (i.e they have the same slope and y intercept)
In our case, if you compare eq 1 and eq 2, the way to make both equations the same line is if b = -6. (this is the answer)